Peran kebudayaan lokal dalam menghadapi globalisasi: Strategi Pelestarian Budaya Lokal di Tengah Arus Global - Augustine, Karima Audy (Maliki Interdisciplinary Journal, 2025)
Globalization has influenced many aspects of society, including culture. Local culture, which has long served as a national identity, is now starting to be marginalized by foreign cultures introduced through media, technology, and modern lifestyles. This article discusses how Indonesian local culture can continue to thrive amidst the rapid flow of globalization. To explain the role of youth, communities, and the government in preserving culture, the author uses a descriptive method based on various literature sources. The findings show that local culture can survive and grow without losing its core values through collaboration and context-based approaches, such as the use of technology and cultural education. In short, local culture should not be seen as outdated, but rather as a strength in facing the global era.